Twenty-first century perspectives on indigenous studies
1 online resource (vi, 270 pages)
Keywords: "In recent years, the interdisciplinary fields of Native North American and Indigenous Studies have reflected, at times even foreshadowed and initiated, many of the influential theoretical discussions in the humanities after the "transnational turn." Global trends of identity politics, performativity, cultural performance and ethics, comparative and revisionist historiography, ecological responsibility and education, as well as issues of social justice have shaped and been shaped by discussions in Native American and Indigenous Studies. This volume brings together distinguished perspectives on these topics by the Native scholars and writers Gerald Vizenor (Anishinaabe), Diane Glancy (Cherokee), and Tomson Highway (Cree), as well as non-Native authorities, such as Chadwick Allen, Hartmut Lutz, and Helmbrecht Breinig. Contributions look at various moments in the cultural history of Native North America--from earthmounds via the Catholic appropriation of a Mohawk saint to the debates about Makah whaling rights--as well as at a diverse spectrum of literary, performative, and visual works of art by John Ross, John Ridge, Elias Boudinot, Emily Pauline Johnson, Leslie Marmon Silko, Emma Lee Warrior, Louise Erdrich, N. Scott Momaday, Stephen Graham Jones, and Gerald Vizenor, among others. In doing so, the selected contributions identify new and recurrent methodological challenges, outline future paths for scholarly inquiry, and explore the intersections between Indigenous Studies and contemporary Literary and Cultural Studies at large"--